2008
DOI: 10.1124/jpet.108.141044
|View full text |Cite
|
Sign up to set email alerts
|

l-Methionine Toxicity in Freshly Isolated Mouse Hepatocytes Is Gender-Dependent and Mediated in Part by Transamination

Abstract: L-Methionine (Met) has been implicated in parenteral nutritionassociated cholestasis in infants and, at high levels, it causes liver toxicity by mechanisms that are not clear. In this study, Met toxicity was characterized in freshly isolated male and female mouse hepatocytes incubated with 5 to 30 mM Met for 0 to 5 h. In male hepatocytes, 20 mM Met was cytotoxic at 4 h as indicated by trypan blue exclusion and lactate dehydrogenase leakage assays. Cytotoxicity was preceded by reduced glutathione (GSH) depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 32 publications
3
40
1
Order By: Relevance
“…Some reports relate l-methionine toxicity with elevated transamination, leading to elevated MT levels [74,75]. Toxicity of MT has been ascribed to inhibition of certain enzymes [76,77].…”
Section: Dlmmentioning
confidence: 98%
“…Some reports relate l-methionine toxicity with elevated transamination, leading to elevated MT levels [74,75]. Toxicity of MT has been ascribed to inhibition of certain enzymes [76,77].…”
Section: Dlmmentioning
confidence: 98%
“…KMTB is then oxidatively decarboxylated to 3-methylthiopropionate (MTP) through an irreversible reaction catalyzed by the branched chain 2-oxo acid dehydrogenase complex (BCKDC) (15). MTP is further metabolized to the gaseous methanethiol (16), which has been reported to then be broken down into simpler molecules, including hydrogen sulfide, dimethyl sulfide, and formic acid, with the end products being carbon dioxide and sulfur dioxide (17,18). Although initial reports on methionine transamination suggested that it provides a route for the degradation and clearance of methionine (19), more recently researchers have claimed that transsulfuration serves as the major pathway for the detoxification of excessive methionine (20).…”
mentioning
confidence: 99%
“…There are many reports of gender being a critical factor in drug-induced liver injury (Hemieda, 2007;McConnachie et al, 2007;Dever, Elfarra, 2008). Moreover, most of those reports demonstrate that males were more susceptible to hepato toxin-induced liver injury than females.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, most of those reports demonstrate that males were more susceptible to hepato toxin-induced liver injury than females. Studies have reported that bioactivation and estrogen concentration are mainly responsible for the gender-dependent discrepancy in liver injury (McConnachie et al, 2007;Dever, Elfarra, 2008;Liang et al, 2011). Also, gender differences in pharmacokinetics and pharmacodynamics characterize many drugs and contribute to individual differences in drug efficacy and toxicity.…”
Section: Resultsmentioning
confidence: 99%